2016
DOI: 10.1080/1343943x.2016.1246064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poultry manure on soil solution electrical conductivity and early growth of Monochoria vaginalis

Abstract: We investigated the effect of poultry manure (PM) on the occurrence and early growth of Monochoria vaginalis in relation to soil solution electrical conductivity (SSEC). PM was applied at rates corresponding to 0 g of nitrogen (N) m −2 (PM-0), 1 g N m −2 (PM-1), 3 g N m −2 (PM-3), and 5 g N m −2 (PM-5). At 7 d post-seeding, the soil solution was sampled to measure EC, and also the emergence and growth of M. vaginalis were evaluated. The emergence rate of M. vaginalis decreased with increasing application rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…However, the addition of Activit to the soil increased its electrical conductivity (EC) above the critical value of 4 mS cm −1 . Watanabe et al [50], in evaluating the effect of chicken manure on soil conductivity, found that the use of chicken manure stimulated the buildup of soluble salts in the soil, as was also demonstrated in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the addition of Activit to the soil increased its electrical conductivity (EC) above the critical value of 4 mS cm −1 . Watanabe et al [50], in evaluating the effect of chicken manure on soil conductivity, found that the use of chicken manure stimulated the buildup of soluble salts in the soil, as was also demonstrated in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results have been reported by other researchers, who attributed the differences found among organic sources to the different induction of soil enzyme activities, soil microbial community composition, soil plant hormone concentration, nutrient use efficiency, etc. [50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%